Modeling Opportunity Costs of Conservation in Transitional Landscapes - Naidoo, R.; Adamowicz, W.L.
Conservation scientists recognize the urgency of incorporating opportunity costs into conservation planning. Despite this, applications to date have been limited, perhaps partly because of the difficulty in determining costs in regions with limited data on land prices and ownership.We present methods for estimating opportunity costs of land preservation in landscapes or ecoregions that are a changing mix of agriculture and natural habitat. Our approach d erives from the literature on estimating land values as opportunity costs of alternate land uses and takes advantage of general availability of necessary data, even in relatively datapoor regions. The methods integrate probabilities of habitat conversion with region-wide estimates of economic benefits from agricultural land uses and estimate land values with a discount rate to convert annual values into net present values.We applied our method in a landscape undergoing agricultural conversion in Paraguay. Our model of opportunity costs predicted an independent data set of land values and was consistent with implicit discount rates of 15-25
Keywords: AGRICULTURAL CONVERSION; CONSERVATION PLANNING; DEFORESTATION; DEVELOPING COUNTRY; LANDSCAPE; MAPPING; PARAGUAY